MODEL PROBLEM BASED LEARNING DALAM PENDIDIKAN AGAMA ISLAM: SUATU STUDI EVALUATIF - Maghfirah, Maghfirah; Walidin, Warul; Mahmud, Salami (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
Educators should choose a learning model that can generate students’ enthusiasm for learning and develop their potential so that they are able to solve the problems faced in life. Problem Based Learning is one of learning models that is considered can maximize the students’ potential and guide them to have the ability to solve problems in life. Problem Based Learning (PBL) is based on constructivism and accommodates students' involvement in the learning process and problem solving. To apply PBL in the learning process, there are several principles and procedures that must be understood by educators. To implement PBL in the learning process, educators should follow the procedures or implementation stages. The procedure for implementing PBL is divided into several steps, namely: problem orientation, organizing students to study (in groups), investigation or data collection, developing and presenting work results and finally; evaluation and reflection. This PBL model certainly has advantages and disadvantages, so educators should study all things related to this PBL to maximize results and minimize deficiencies, educators should adhere to the principles and procedures for implementing them in the learning process because PBL is one of the learning models that is capable to answer the needs of students and be relevant to the demands of this century.